2009
DOI: 10.2169/internalmedicine.48.1677
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Triglyceride Value in the Diagnosis and Treatment Response of Secondary Hemophagocytic Syndrome

Abstract: Background/Aims Secondary hemophagocytic syndrome (hemophagocytic lymphohistiocytosis, HLH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 28 publications
(19 reference statements)
2
32
0
2
Order By: Relevance
“…(5) The disease is classified as primary or secondary HPS. (6) The two forms are clinically indistinguishable, being characterized by a sepsis-like presentation with splenomegaly, cytopenia, hyperferritinemia, bleeding disorder, and hemophagocytosis. Consequently, multiorgan failure often develops, leading to high mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) The disease is classified as primary or secondary HPS. (6) The two forms are clinically indistinguishable, being characterized by a sepsis-like presentation with splenomegaly, cytopenia, hyperferritinemia, bleeding disorder, and hemophagocytosis. Consequently, multiorgan failure often develops, leading to high mortality.…”
Section: Discussionmentioning
confidence: 99%
“…(7) Primary HPS is hereditary, and most patients present with symptoms within two years after birth, being treated in the pediatric field. (6) The primary form of HPS has an autosomal recessive pattern of inheritance, with an incidence of approximately 1/50,000 live births. (7) Primary HPS can result from autosomal defects or be associated with immune deficiencies, such as Chediak-Higashi syndrome, X-linked lymphoproliferative syndrome, and Griscelli syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring the triglyceride level is a recently defined follow-up parameter in the evaluation of treatment response in secondary HLH as reported by Okamoto et al [17]. Sarper et al [18] reported low triglyceride levels in 2 patients diagnosed with HLH.…”
Section: Discussionmentioning
confidence: 99%
“…24 Triglycerides have been evaluated as a diagnostic and prognostic marker for HLH with good sensitivity. 25 In present study diagnosis of HLH was done based on HLH 2004 criteria. We have not performed genetic and molecular analysis, NK cell activity and soluble IL2 receptor levels because of nonavailability.…”
Section: Diagnostic Criteriamentioning
confidence: 99%